Coated separator, manufacturing method for coated separator, and battery
By introducing multi-layer structures and ceramic particles into the coating, the problem of uneven distribution of one-dimensional nanomaterials in the coating is solved, the lithium ion conductivity and thermal stability of the battery are improved, and the battery performance is improved.
Patent Information
- Application Number
- JP2024566702
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-21
- Filing Date
- 2022-07-28
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2042-07-28
AI Technical Summary
In the prior art, the one-dimensional nanomaterial dispersed coatings are unevenly distributed, resulting in a large number of voids and low contact points in the diaphragm, affecting the thermal stability and lithium ion conductivity of the diaphragm.
A multi-layer structure coating design is adopted, combining one-dimensional nanomaterials and ceramic particles, where the length of the one-dimensional nanomaterial is shortened layer by layer, and a uniformly distributed coating structure is formed by controlling the particle size and proportion of the ceramic particles to improve lithium ion conductivity.
It effectively reduces the void caused by uneven distribution in the coating, enhances the lithium-ion conductive channel, and improves the thermal stability and battery performance of the separator.
Smart Images

Figure 2025503328000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of battery separator technology, and more particularly to coated separators, methods for making coated separators, and batteries. [Background technology]
[0002] The separator is one of the main components of lithium batteries, and its performance has a very important impact on the overall performance of lithium batteries, and is one of the key technologies that restrict the development of lithium batteries. As the application fields of lithium batteries continue to expand and the impact of lithium battery products on people's lives continues to become more and more serious, people's requirements for lithium battery performance are also increasing. In order to meet the development requirements of lithium batteries, the separator, as an important component of lithium batteries, not only should have good chemical stability and low manufacturing cost, but also further improve the safety performance of lithium-ion batteries, which is an important trend in the current development of lithium batteries.
[0003] In conventional related technologies, a coated separator may include a base membrane and a coating layer coated on at least one surface of the base membrane, and the coating layer may include a one-dimensional nanomaterial; however, the deposition manner of the one-dimensional nanomaterial is messy and irregular, which is prone to problems such as too many voids and too few contact points, thereby affecting the thermal stability of the separator. Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention provides a coated separator, a method for producing the coated separator, and a battery in order to improve the performance of the separator. [Means for solving the problem]
[0005] According to a first aspect of the present invention, there is provided a coated separator comprising a base membrane and a coating layer structure provided on at least one surface of the base membrane, the coating layer structure comprising multiple material layers, the coating layer structure comprising one-dimensional nanomaterial and ceramic particles, and the average length of the one-dimensional nanomaterial in each material layer decreases with each layer along a direction away from the base membrane.
[0006] Alternatively, the thickness of the coating layer in which the ceramic particles are distributed accounts for 80% or more, preferably 90% or more, and more preferably 100% of the total thickness of the coating layer structure.
[0007] Optionally, the mass ratio of the one-dimensional nano material to the ceramic particles in the coating layer structure is 1:1 to 1:14.
[0008] Optionally, the ceramic particles include first ceramic particles and second ceramic particles, where the particle size of the second ceramic particles is larger than the particle size of the first ceramic particles, and the particle size of the second ceramic particles is larger than a diameter of the one-dimensional nanomaterial; Furthermore, the particle diameter of the second ceramic particles is at least twice the diameter of the one-dimensional nanomaterial; Furthermore, the particle size of the second ceramic particles and the linear relationship between the particle size and the one-dimensional nanomaterial are Diameter and front The first ceramic particle At least one of the particle sizes and One digit End There is a difference between Furthermore, the one-dimensional nanomaterial has a diameter of 5 to 50 nm, the first ceramic particles have an average particle size of 10 to 60 nm, and the second ceramic particles have an average particle size of 100 to 600 nm.
[0009] Optionally, in the coating layer structure, a mass ratio of the first ceramic particles to the second ceramic particles is 5:1 to 1:5.
[0010] Optionally, the first ceramic particles and Before The second ceramic particle At least one of It is an inorganic substance that has a melting point of 200°C or higher, is electrically insulating, and is electrochemically stable within the range of use of lithium batteries.
[0011] Optionally, lithium ion conductive functional groups are grafted onto the surfaces of the first ceramic particles; Furthermore, the lithium ion conductive functional group includes any one of hydroxyl (-OH), carbonyl (-C=O), fluorine (-F) and carboxyl (-COOH).
[0012] Optionally, the coating separator comprises at least: a) Puncture resistance of the coating layer force ≧7N, b) ionic conductivity ≧0.8; c) Capacity maintenance rate ≧90%, d) Thermal shrinkage at 180℃ / h ≦4%; Satisfy one of the following conditions.
[0013] According to a second aspect of the present invention, there is provided a method for producing a coated separator according to the first aspect and its alternative solution, the method comprising the steps of: particle The method includes the steps of dispersing the nanomaterial, dispersing the one-dimensional nanomaterial, mixing to prepare a paste, and coating to form a film. Ceramics particle In the dispersion of the ceramic particles, the ceramic particles are dispersed in a first solvent, and the ceramic particles are particle Obtain a dispersion, In dispersing one-dimensional nanomaterials, one-dimensional nanomaterials of different lengths are dispersed in the same or different dispersants to obtain at least one one-dimensional nanomaterial dispersion; In the preparation of the paste by mixing, the ceramic particle dispersion liquid and The one-dimensional nanomaterial dispersion By preparing a mixed solution containing , forming at least one corresponding paste; In the film formation by coating, the at least one paste is coated onto at least one surface of the base film, and then dried to obtain the coated separator.
[0014] Optionally, ceramics particle Before dispersion, ceramics particle The method further comprises the step of selecting Ceramics particle In the selection step, first ceramic particles and second ceramic particles having different particle sizes are selected, wherein the first ceramic particles have an average particle size of 10 to 60 nm, and the second ceramic particles have an average particle size of 100 to 600 nm; In addition, ceramics particle The method further comprises the steps of: particle In the pretreatment, the first ceramic particles are added to a second solvent and then placed in a reaction vessel, and a grafting target is added to carry out a grafting reaction, thereby grafting lithium ion conductive functional groups onto the surface of the first ceramic particles.
[0015] Optionally, the grafting object includes any one of polycarbonate, polylactic acid, polyurethane, perfluoropropyl vinyl ether, and methyl isopropyl ketone.
[0016] According to a third aspect of the present invention, there is provided a battery comprising a coated separator according to the first aspect and its alternative solutions, or comprising a coated separator produced by the method for producing a coated separator according to the second aspect and its alternative solutions, Furthermore, the battery is a lithium battery. Effect of the Invention
[0017] In the coated separator, the manufacturing method of the coated separator, and the battery provided by the present invention, the one-dimensional nanomaterials in each material layer have an average length that is shorter for each layer and are regularly distributed, so that the formation of large voids that may be caused by the disorderly and irregular distribution of the one-dimensional nanomaterials can be avoided. Meanwhile, in order to prevent the stacking density of the one-dimensional nanomaterials from being too high and affecting the conduction of lithium ions, the present invention adds ceramic particles to the coating layer structure, so that the coating layer structure is a mixture of the one-dimensional nanomaterials and the ceramic particles, and by adding the ceramic particles, the stacking density of the one-dimensional nanomaterials can be prevented from being too high, so that an effective lithium ion conduction channel can be formed, so that the conductivity of lithium ions can be improved, and the performance of the separator and the battery can be effectively improved. [Brief description of the drawings]
[0018] In the following, in order to more clearly describe the embodiments of the present invention or the technical solutions in the prior art, the drawings that need to be used in the description of the embodiments or the prior art will be briefly described. Of course, the drawings in the following description are only some embodiments of the present invention, and those skilled in the art can obtain other drawings based on these drawings without any creative efforts. [Figure 1] FIG. 2 is a schematic diagram of the local structure of a coating separator in one embodiment of the present invention. [Diagram 2] 4 is a flowchart of a method for manufacturing a coating separator in one embodiment of the present invention. [Diagram 3] FIG. 1 is a schematic diagram showing a case where the length value of the material layer l50 in a specific embodiment of the present invention varies according to the position of the coating layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, the technical solutions in the embodiments of the present invention will be described clearly and completely with reference to the drawings of the embodiments of the present invention, and it is to be understood that the described embodiments are only a part of the embodiments of the present invention, and are not all of the embodiments. Based on the embodiments of the present invention, all other embodiments that a person skilled in the art can obtain without any creative effort shall be within the scope of protection of the present invention.
[0020] In addition, in the description of the present invention, the orientations or positional relationships indicated by the terms "upper", "lower", "upper end", "lower end", "lower surface", "top surface", etc. are orientations or positional relationships shown based on the drawings, and are merely intended to easily explain and simplify the description of the present invention, and do not indicate or imply that the devices or elements shown must have a specific direction and be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention.
[0021] In describing the present specification, it is to be understood that the terms "first" and "second" are for descriptive purposes only and do not indicate or imply a relative importance or number of the technical features indicated, whereby a feature qualified by "first" or "second" may explicitly or implicitly include one or more of said features.
[0022] In the present description, "plurality" means a large number, for example, two, three, four, etc., unless otherwise specified.
[0023] In the description of the present invention, the term "connection" should be understood in a broad sense unless otherwise clearly specified and limited, and may be, for example, a fixed connection, a removable connection, or an integrated one, a mechanical connection, an electrical connection, or a connection capable of communicating with each other, a direct connection, an indirect connection via an intermediate medium, an internal communication between two elements, or an interaction between two elements. Those skilled in the art can understand the specific meaning of the above terms in the present invention according to the specific circumstances.
[0024] The technical solutions of the present invention will be described in detail below with reference to specific embodiments, which can be combined with each other, and the same or similar concepts or processes may be omitted in some embodiments.
[0025] Before proposing the present application, the applicant conducted a series of studies and experiments on conventional separators. In order to solve problems such as the deposition method of the one-dimensional nano material in the coating layer being messy and irregular, which is likely to cause too many voids and few contact points, the applicant provides a corresponding solution, in which the length of the one-dimensional nano material is gradually decreased layer by layer according to the coating layer (embodied in the gradually decreasing length description value of the one-dimensional nano material of each material layer), and because the voids deposited by the long nano material are large, the lower the layer, the larger the voids are, and the shorter nano material in the upper layer can fill these voids to a certain extent. When deposited layer by layer, there are not so many voids inside the coating layer, and the contact points are increased, so that when exposed to heat, the dense structure of the coating layer can suppress the occurrence of thermal deformation of the separator, thereby improving the heat resistance of the coated separator. Regarding this solution, the applicant has also proposed a patent application (application number: PCT / CN2022 / 077087, filing date: 2022.02.21), which hereby incorporates all the contents of PCT / CN2022 / 077087, i.e., all the contents of PCT / CN2022 / 077087 may serve as support for this application.
[0026] However, the applicant found through further research that, although the above solution can improve the heat resistance of the separator compared to the method in which the one-dimensional nanomaterials are randomly arranged, the overall performance of the separator is still not ideal. Length They found that a deposition method in which the density of the nanofibers gradually decreases with each layer can maximize the density of the coating layer and maximize the contact between the nanofibers. However, if the deposition density of the one-dimensional nanofibers is too high, it can block the lithium ion conduction channel and affect the lithium ion conductivity, limiting the performance of the separator.
[0027] Based on this discovery, the applicant has obtained the technical solution of the present application through a series of research, testing and verification. Since the regular arrangement of one-dimensional nanofibers is the applicant's main technical innovation, the further researched problems and the obtained solutions based on the regular arrangement are also main technical innovations, and the entire research process should be an inseparable part of the solution and should be considered as a whole when assessing the inventive step of the present application.
[0028] Referring to FIG. 1, an embodiment of the present invention provides a coating separator 1, which includes a base film 11 and a At least one surface of and a coating layer structure 12 provided on the base film, the coating layer structure 12 including multiple material layers, in which one-dimensional nanomaterials and ceramic particles 13 are distributed, and along the direction away from the base film, the average length of the one-dimensional nanomaterials in each material layer becomes shorter from layer to layer, and correspondingly, the average size of the voids in the one-dimensional nanomaterials in each material layer also gradually becomes smaller.
[0029] In the present embodiment, the ion conduction rate can be effectively improved by introducing ceramic particles in consideration of the problem that if the coating layer of the one-dimensional nano material is too dense, the voids become too small, resulting in a low ion conduction rate. However, if the one-dimensional nano material is irregularly distributed, , Se Lamix particles Add more When the 1D nanomaterial is introduced, it is likely to cause irregular mixing, so that the lithium ion conduction channel in some regions is small and the lithium ion conduction channel in some regions is large, which leads to a large difference in the conduction speed of lithium ions in different regions, which is likely to cause problems in the growth and development of lithium dendrites (easy to cause self-discharge), and further leads to battery capacity decay and safety problems. In the present application, in order to shorten the average length of the 1D nanomaterial in each material layer layer by layer, ceramic particles are mixed into the 1D nanomaterial, and the use of ceramic particles can avoid the stacking density of the 1D nanomaterial being too large, so that a more effective lithium ion conduction channel can be formed, which can improve the conductivity of lithium ions and effectively improve the performance of the separator and the battery.
[0030] In a preferred embodiment, the mass ratio of the one-dimensional nano material to the ceramic particles in the coating layer structure 12 is 1:1 to 1:14. In a specific embodiment, the mass ratio of the one-dimensional nano material to the ceramic particles in the coating layer structure 12 may be, for example, any one of 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14 or any two of these. Of course, the mass ratio of the one-dimensional nano material to the ceramic particles in the coating layer structure 12 may be other values, and the specific values do not limit the present invention, and any ratio between 1:1 and 1:14 is within the scope of the present invention.
[0031] In a preferred embodiment, the ceramic particles in the coating layer structure 12 include first ceramic particles and second ceramic particles, where the particle diameter of the first ceramic particles corresponds to the diameter of the one-dimensional nanomaterial, and the particle diameter of the second ceramic particles is much larger than the diameter of the one-dimensional nanomaterial.
[0032] Specifically, the one-dimensional nanomaterial has a diameter of 5 to 50 nm, the first ceramic particles have an average particle size of 10 to 60 nm, and the second ceramic particles have an average particle size of 100 to 600 nm.
[0033] In an embodiment of the present invention, the 1D nanomaterials are mixed with multi-sized ceramic particles in a hierarchical distribution, such that the 1D nanomaterials at the bottom are longer and the 1D nanomaterials at the top are shorter. In the same material layer, Uniformly distributed, different areas Length By reducing the difference between the sizes, the introduced multi-sized ceramics can sufficiently accelerate the conduction of lithium ions. Here, the layering refers to a layer formed by a significant change in the size of the nanofiber in the thickness direction, and may be a plurality of substantially separable layers, or may be an artificial layering based on a significant size change (for example, a layer occupying 10% of the total thickness of the coating layer is defined as a layer, or a layer occupying 20%, 30%, 40% or the like of the total thickness of the coating layer is defined as a layer, and the definition of the layering may be based on the interface where the size change in the structure is significant, and is not specifically limited here).
[0034] In a preferred embodiment, the thickness of the coating layer in which the ceramic particles 13 are distributed in the coating layer structure 12 accounts for more than 80%, preferably more than 90%, and more preferably 100% of the total thickness of the entire coating layer structure, so that the ceramic particles are relatively uniformly distributed in the coating layer structure, and the stacking density of the one-dimensional nanomaterial is more effectively prevented from being too high, so that a more effective lithium ion conduction channel can be formed, thereby improving the conductivity of lithium ions and effectively improving the performance of the separator and the battery. In addition, in a further preferred embodiment, when there is a clear hierarchy in the coating layer structure, each layer contains ceramic particles, so that the conductivity of lithium ions can be further improved and the performance of the separator and the battery can be improved.
[0035] By setting the average particle size (D50) of the first ceramic particles to be equivalent to the diameter of the one-dimensional nano material, the first ceramic particles can expand the gaps between the one-dimensional nano material, improving the lithium ion conductivity, and by setting the average particle size (D50) of the second ceramic particles to be much larger than the average particle size of the first ceramic particles and the diameter of the one-dimensional nano material, the ability of the coating layer to withstand puncture from the outside can be improved. Here, much larger means more than twice as large. As the applicant has proven through research, if the average particle size of the first ceramic particles is too small, the first ceramic particles will aggregate severely, which will result in a low lithium ion conductivity of the coating, while if the average particle size of the first ceramic particles is too large, the gaps of the one-dimensional nano material cannot be sufficiently filled. If the average particle size of the second ceramic particles is too small, the puncture resistance will decrease, while if the average particle size of the second ceramic particles is too large, the heat resistance of the coating layer will be sacrificed. Therefore, the average particle size of the first ceramic particles proposed in the present application, which is 10 to 60 nm, and the average particle size of the second ceramic particles proposed in the present application, which is 100 to 600 nm, are verified to be preferable values.
[0036] In a specific embodiment, the average particle size of the first ceramic particles may be, for example, any one of 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, or any two of the above. The average particle size of the second ceramic particles may be, for example, any one of 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 375 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, or any two of the above. Of course, the average particle size of the first ceramic particles and the average particle size of the second ceramic particles may be other values, and the specific values do not limit the present invention, and as long as the average particle size of the first ceramic particles is 10-60 nm and the average particle size of the second ceramic particles is 100-600 nm, both are within the scope of protection of the present invention. As a person skilled in the art can understand, when the diameter of the one-dimensional nano material changes, the average particle size of the first ceramic particles and the average particle size of the second ceramic particles also change accordingly, and as long as the particle size of the first ceramic particles corresponds to the diameter of the one-dimensional nano material and the particle size of the second ceramic particles is much larger than the diameter of the one-dimensional nano material, neither will deviate from the scope of protection of the present invention.
[0037] In a further preferred embodiment, the mass ratio of the first ceramic particles to the second ceramic particles in the coating layer structure is 5:1 to 1:5, which can further improve the ionic conductivity of the coating layer and the puncture resistance of the coating layer (puncture resistance of the coating layer). force≧7N) and thermal shrinkage performance (180℃ / 1h≦4%) can be more effectively ensured. The applicant has found through research that if the number of first ceramic particles is too large, the puncture resistance is poor, if the number of first ceramic particles is too small, the expansion is limited and the lithium ion conductivity is reduced, if the number of second ceramic particles is too large, the heat resistance is reduced, and if the number of second ceramic particles is too small, the puncture resistance performance is reduced. Therefore, it has been verified that the mass ratio of the first ceramic particles to the second ceramic particles in the coating layer structure provided in the present application is 5:1 to 1:5, which is a preferred value.
[0038] Specifically, the mass ratio of the first ceramic particles to the second ceramic particles in the coating layer structure may be, for example, any one or any two of 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, and 1:5. Of course, the mass ratio of the first ceramic particles to the second ceramic particles in the coating layer structure may be other values, and the specific values do not limit the present invention, and any ratio between 5:1 and 1:5 is within the scope of the present invention.
[0039] In a more preferred embodiment, lithium ion conductive functional groups are grafted onto the surfaces of the first ceramic particles. Specifically, the lithium ion conductive functional groups are introduced onto the surfaces of the first ceramic particles by a graft reaction. The lithium ion conductive functional groups contained in large quantities on the surfaces of the first ceramic particles can significantly improve the lithium ion conducting ability. The graft functional groups are particle The second ceramic can only act on the surface of the Particle Ceramics with the largest particle size Particle Because the particle size is larger, the gaps formed are large. Lithium ion conductive functional group The first ceramic Particle The small particle size results in small gaps, which improves lithium ion conductivity. functional group The effect of the above is better exerted, and the conductivity of lithium ions is improved.
[0040] The manner in which the length of the one-dimensional nano material in the embodiment of the present invention gradually decreases from layer to layer along the coating layer will be described in more detail as follows.
[0041] Here, the coating layer has three material layers as shown in FIG. 1 (here, the definition of the hierarchical structure is based on the interface where the dimensional change is significant in the coating layer structure), where the one-dimensional nanomaterial of the bottom layer has a longer average length than the one-dimensional nanomaterial of the middle layer, which has a longer average length than the one-dimensional nanomaterial of the top layer, and the difference in average length between the one-dimensional nanomaterials of each layer can be set arbitrarily, and the lengths of the one-dimensional nanomaterials in the same layer may be the same or different. In one embodiment, the one-dimensional nanomaterial may be at least one of nanocellulose, aramid nanofiber, and polyimide nanofiber. The material selection of the one-dimensional nanomaterial in the embodiment of the present invention is not limited to the above examples.
[0042] In one embodiment, the same second target occupancy of the one-dimensional nanomaterial of the different material layers creates different length description values; The length description of the one-dimensional nanomaterial in the layer of material is When the number of one-dimensional nanomaterials in the material layer structure is accumulated in order from shortest to longest, the ratio of the number obtained by accumulating the number to the total number of one-dimensional nanomaterials in the material layer reaches the second target occupancy ratio, which indicates the length of the corresponding one-dimensional nanomaterial, and accordingly, in the one-dimensional nanomaterial of the corresponding material layer, the length is shorter than the corresponding length description value. Length The occupancy ratio of the one-dimensional nanomaterial can reach the target occupancy ratio, and the above explanation shows the statistical meaning of the length description value of the one-dimensional nanomaterial, and when actually trying to determine the length description value, the actual calculation method can be processed based on common sense in the field.
[0043] In one example, the second target occupancy ratio is in the range of 5% to 40% or in the range of 60% to 99%. For example, it may be any one of 5%, 10%, 20%, 40%, 60%, 70%, 80%, 90%, and 99%, or a range between any two of them.
[0044] In one embodiment, along a direction away from the base film, for the same second target occupancy ratio, the length description value of the one-dimensional nanomaterial of each layer of material is gradually reduced. Length It is possible to form a trend that decreases with each layer.
[0045] In addition, with regard to the length description value of the corresponding material layer, the meaning of the length description value is defined above by accumulating and determining the length description value based on the accumulation result, but this does not indicate that this statistical process is necessarily included in the actual manufacturing and inspection process, and in an actual solution, as long as the rule of the length description value obtained after stating the one-dimensional nanomaterial in the material layer with the same statistically meaningful numerical value for any product satisfies the above description, it does not deviate from the scope of protection of the embodiment. In some solutions, the satisfaction of the above length rule can be ensured by selecting the length of the one-dimensional nanomaterial in advance or manufacturing according to the length of the one-dimensional nanomaterial.
[0046] Where: For the length description value of a one-dimensional nanomaterial of a material layer, e.g. The term "l10" for one-dimensional nanomaterials in a material layer refers to the length of one-dimensional nanomaterials when the ratio of the number obtained by sequentially accumulating the number of one-dimensional nanomaterials of each length in the corresponding material layer in order of shortest length to the total number of one-dimensional nanomaterials in the corresponding material layer reaches 10%, The l50 of the one-dimensional nanomaterial in the material layer means the length of the one-dimensional nanomaterial when the ratio of the number obtained by sequentially accumulating the number of one-dimensional nanomaterials of each length in the corresponding material layer in order of shortest length to the total number of one-dimensional nanomaterials in the corresponding material layer reaches 50%, and the l50 may be understood to some extent to indicate the average length of the corresponding material layer; The l90 of a one-dimensional nanomaterial in the material layer means the length of the one-dimensional nanomaterial when the ratio of the number obtained by sequentially accumulating the number of one-dimensional nanomaterials of each length in the corresponding material layer in order of shortest length to the total number of one-dimensional nanomaterials in the corresponding material layer reaches 90%.
[0047] When a reduction in l50 (ie, the average length) is achieved, a reduction in one or more other length description values (eg, l90 and / or l10) may also be achieved.
[0048] In one embodiment, The length value L10 of the one-dimensional nano material in the coating layer structure is between 100 and 300 nm; The length value L50 of the one-dimensional nanomaterial in the coating layer structure is between 250 and 400 nm; The length value L90 of the one-dimensional nanomaterial in the coating layer structure is between 350 and 900 nm; Where: L10 of the one-dimensional nanomaterial in the coating layer structure indicates a length description value of the one-dimensional nanomaterial in the coating layer structure when 10% is a first target occupancy ratio; L50 of the one-dimensional nanomaterial in the coating layer structure indicates a length description value of the one-dimensional nanomaterial in the coating layer structure when 50% is a first target occupancy ratio, and may be understood as the average length of the one-dimensional nanomaterial in the coating layer structure; L90 of the one-dimensional nanomaterial in the coating layer structure represents a length description value of the one-dimensional nanomaterial in the coating layer structure when 90% is a first target occupancy ratio; The length description of the one-dimensional nanomaterial in the coating layer structure is the length of the one-dimensional nanomaterial corresponding to the ratio of the number obtained by sequentially accumulating the number of one-dimensional nanomaterials in the coating layer structure in order of shortest length to the total number of one-dimensional nanomaterials in the coating layer structure reaches the first target occupancy ratio; and the one-dimensional nano-material in the coating layer structure satisfies L50 / L10>1.3, L90 / L50>1.3; L10 of the one-dimensional nanomaterial in the coating layer structure means a length description value of the one-dimensional nanomaterial in the coating layer structure when the first target occupancy ratio is 10%, L50 of the one-dimensional nanomaterial in the coating layer structure means a length description value of the one-dimensional nanomaterial in the coating layer structure when 50% is a first target occupancy ratio; L90 of the one-dimensional nanomaterial in the coating layer structure means a length description value of the one-dimensional nanomaterial in the coating layer structure when 90% is a first target occupancy ratio; The above description shows the statistical meaning of the length description value of the coating layer structure, and when actually determining the length description value, the actual calculation method can be processed according to common knowledge in the art.
[0049] Furthermore, with regard to the length description value of the coating layer structure, the meaning of the length description value is defined above by accumulating and determining the length description value based on the accumulation result, but this does not indicate that this statistical process is necessarily included in the actual manufacturing and inspection process, and in an actual solution, if the rule of the length description value obtained after stating the one-dimensional nanomaterial in the material layer with the same statistically meaningful numerical value for any product satisfies the above description, it does not deviate from the scope of protection of the embodiment. In some solutions, the satisfaction of the above length rule can be ensured by selecting the length of the one-dimensional nanomaterial in advance or manufacturing according to the length of the one-dimensional nanomaterial.
[0050] In one example, for the one-dimensional nanomaterials in the coating layer structure, L10=110 nm, L50=310 nm, and L90=850 nm.
[0051] In the direction away from the base film, the fitting results of the relationship between the length value l50 of the one-dimensional nanomaterial in each material layer and the position in the coating layer where the material layer is located (the position in the thickness direction of the coating layer) can be understood by referring to curves 1, 2a, and 2b in Figure 3, and further embodied in the curves is that this length value l50 gradually becomes smaller as the thickness increases (i.e., as the distance between the position in the coating layer where the material layer is located and the base film increases).
[0052] In Figure 3, the position of the coating layer on the horizontal axis is intended to indicate the position of the coating layer where the material layer is located in the coating layer structure along the thickness direction, and when expressed as a percentage, it can indicate the percentage that the distance between the coating layer position where the material layer is located and the base film accounts for in the entire thickness of the coating layer structure, for example, 10% here indicates that the distance between the coating layer position and the base film accounts for 10% of the entire thickness of the coating layer structure.
[0053] For curve 1, the length value of l50 of the one-dimensional nanomaterial in the material layer changes linearly with the increase in the distance between the position of the coating layer where the material layer is located and the base film. Good morning In this case, the relationship between the length value x of l50 and the position Y of the coating layer can be expressed as, for example, Y=kx+b (k<0, b>0), For curve 2a, the length value l50 of the one-dimensional nanomaterial in the material layer may tend to change faster at first and then slower with the increase in the distance between the position of the coating layer where the material layer is located and the base film; For curve 2b, the length value l50 of the one-dimensional nanomaterial in the material layer can tend to change slowly at first and then change faster as the distance between the position of the coating layer where the material layer is located and the base film increases.
[0054] In order to realize the above linear change tendency, the tendency to change quickly at first and then change slowly, or the tendency to change slowly at first and then change quickly, it can be realized by setting the length of the one-dimensional nano material in the coating layer structure. Furthermore, the setting of the length of the one-dimensional nano material in the coating layer structure can be selected according to the required change tendency, for example, If it is necessary to realize a linear change (for example, as shown in curve 1), the length setting of the one-dimensional nanomaterial in the coating layer structure must satisfy 2≧L90 / L50>1.5; If it is necessary to realize a slow change at first and then a fast change (for example, as shown in curve 2b), the length setting of the one-dimensional nanomaterial in the coating layer structure should satisfy L50 / L10>2, 1.5≧L90 / L50≧1.3; If it is necessary to realize an initial fast change and then a slower change (for example, as shown in curve 2a), the coating layer structure The length setting of the one-dimensional nanomaterial in the nanostructure must satisfy L90 / L50>2.
[0055] Since the prior art does not devise a method for forming a layered structure, the prior art cannot disclose or suggest the setting of the length according to different change trends in the above solutions.
[0056] Moreover, an embodiment of the present invention further provides a battery including a coated separator according to the above optional solution.
[0057] Also, referring to FIG. 2, an embodiment of the present invention further provides a method for manufacturing a coated separator according to the first aspect and its optional solution, and the method includes the following steps S1 to S4.
[0058] S1 Ceramics particle In the dispersion of the ceramic particles, the ceramic particles are dispersed in a first solvent, and the ceramic particle A dispersion is obtained.
[0059] Specifically, ceramic particles are dispersed in a first solvent to obtain a dispersion liquid. The medium is , water, N-methylpyrrolidone, ethanol, acetone, etc. It is one of the choices from . Ceramic Particles The ceramic particles are uniformly dispersed in the solvent using high-speed stirring, high-pressure homogenization, sand mill dispersion, etc., and the mass concentration of the ceramic particles in the dispersion is 2% to 40%.
[0060] In dispersing the one-dimensional nanomaterials in step S2, one-dimensional nanomaterials of different lengths are dispersed in the same or different dispersants to obtain at least one kind of one-dimensional nanomaterial dispersion.
[0061] Specifically, one-dimensional nanomaterials of different lengths are dispersed in a dispersant to obtain a dispersion. The agent , water, N-methylpyrrolidone, ethanol, acetone, etc. It is one of the choices from . 1D Nanomaterials The one-dimensional nanomaterials are uniformly dispersed in the dispersion medium by using methods such as high-speed stirring, high-pressure homogenization, and sand mill dispersion, and the mass concentration of the one-dimensional nanomaterials in the dispersion medium is 2% to 30%.
[0062] Here, one-dimensional nanomaterials of at least partially different lengths are realized depending on the selection of raw materials for the one-dimensional nanomaterial, for example, when one-dimensional nanomaterials of different materials are selected and used, one-dimensional nanomaterials of different lengths may be formed.
[0063] In another example, one-dimensional nanomaterials of different lengths may be formed by related technological means.
[0064] One-dimensional nanomaterials of at least partially different lengths can be formed by cutting a starting one-dimensional nanomaterial or a cut one-dimensional nanomaterial, either in one or multiple cuts.
[0065] Here, by cutting the one-dimensional nanomaterial, a short one-dimensional nanomaterial can be formed based on a length of one-dimensional nanomaterial raw material, for example, the one-dimensional nanomaterial can be cut in half of the raw material, or in other examples, it can be achieved without adopting the method of cutting in half.
[0066] Any existing or improved means capable of achieving cutting of a one-dimensional nanomaterial can be embodied in the embodiments of the present invention, in which the cutting can be achieved by etching the one-dimensional nanomaterial, for example, by etching the one-dimensional nanomaterial to half its original length.
[0067] Depending on the desired layering, a single cut or multiple cuts can be made to the feedstock, for example, by first etching the one-dimensional nanomaterial to half the length of the feedstock, and then Part Half-length 1D nanomaterials are reserved, and other portion In another embodiment, a portion of the one-dimensional nanomaterial that is one-quarter of the length may be cut, and the number of cuts may be arbitrarily set according to needs.
[0068] Naturally, One Other raw materials for 1D nanomaterials One 1D nanomaterial Joining to one end of the raw material, One of bonded 1D nanomaterials One 1D nanomaterial Joining to one end of the raw material, One Other applications of bonded 1D nanomaterials One At least one step of bonding may be performed, with bonding to one end of the bonded one-dimensional nanomaterial, to form one-dimensional nanomaterials of at least partial different lengths through one or more bondings.
[0069] Thus, the object of joining is One 1D nanomaterial One end of the raw material and the other One 1D nanomaterialIt may be a part of the raw material, One 1D nanomaterial It may be one end of a raw material and one end of a bonded one-dimensional nanomaterial, or it may be one end of a bonded one-dimensional nanomaterial and one end of another bonded one-dimensional nanomaterial.
[0070] Here, by joining to the one-dimensional nanomaterial, a long one-dimensional nanomaterial can be formed based on one length of one-dimensional nanomaterial raw material, for example, two One-dimensional nanomaterials By joining the feedstocks together, one-dimensional nanomaterials of double length may be formed, and in other instances, one-dimensional nanomaterials of different lengths may be formed. One-dimensional nanomaterials This may be achieved using raw materials (or grafted 1D nanomaterials).
[0071] Any existing or modified means capable of achieving joining of one-dimensional nanomaterials may be embodied in embodiments of the present invention.
[0072] For example, the conjugation of one-dimensional nanomaterials may be realized based on materials with a high content of hydroxyl functional groups (e.g. polyethylene glycol PEG), in which case the conjugation mentioned above may be achieved by: Mixing the one-dimensional nanomaterial to be conjugated and a material with a large amount of hydroxyl functional groups (e.g., PEG) in a solution; adding molecular sieve particles as a catalyst to the solution; heating and cooling the solution and filtering out the molecular sieves to obtain the grafted one-dimensional nanomaterial.
[0073] In a specific example, nanocellulose is used as an example. S The end region has a significantly higher hydroxyl content than the middle region. The activity of hydroxyls can be fully exerted to increase the length of nanocellulose, and the method is as follows: (1) Nanocellulose is mixed with polyethylene glycol (PEG), the molecular weight of PEG is 50,000 to 1,000,000 g / mol, and PEG is the nanocellulose. Mass1%, and then thoroughly and uniformly mix the two to form the corresponding solution. (2) adding 13A molecular sieve particles to the solution, the particle size being 1 mm to 10 mm, the molecular sieve being a catalyst; (3) 80 over 1-2 hours ℃ to water bath Heat with (4) The mixture is cooled to room temperature and the 13A molecular sieve particles are filtered off to obtain the grafted nanocellulose.
[0074] In the above solution, the nanocellulose can be cross-linked by adding a material (such as PEG) containing a large amount of hydroxyl functional groups, and the polymerization reaction between PEG and nanocellulose can be accelerated by using molecular sieves (such as 13A molecular sieves) as a catalyst, and finally a nanocellulose-PEG-nanocellulose structure is formed. According to the desired layering, one or multiple bondings can be realized for the raw material, for example, the raw material of the one-dimensional nanomaterial is first bonded to twice the raw material, and then a part of the one-dimensional nanomaterial with twice the length is reserved, and the other one-dimensional nanomaterial with twice the length is bonded to the raw material or the one-dimensional nanomaterial with twice the length to obtain a one-dimensional nanomaterial with three or four times the length, at which time a three-layer structure can be formed, and in other examples, further bonding can be performed, and the number of bondings can be set arbitrarily as needed.
[0075] In one solution for step S2, one-dimensional nanomaterials of various lengths may be dispersed in the same dispersant, thereby realizing hierarchical formation after coating based on pastes corresponding to the same dispersant; in another solution for step S2, different dispersions may be formed based on one-dimensional nanomaterials of different lengths (the lengths of the one-dimensional nanomaterials in the different dispersants are different), thereby forming different dispersions and pastes, and during coating, different pastes may be coated layer by layer based on the lengths of the one-dimensional nanomaterials.
[0076] As an example, in step S2, one-dimensional nanomaterials of various lengths may be thoroughly dispersed in a dispersant, The agent , e.g. water, ethanol, methanol, etc. It is one of the choices from Dispersion methods include, for example, ultrasonic treatment, high-speed stirring, high-pressure homogenization, and sand mill dispersion. The dispersion method is as follows. By adopting 1D nanomaterials Disperse evenly in the dispersant do. The concentration in the one-dimensional nanomaterial dispersion may range from 0.01 to 50 wt %.
[0077] In the preparation of a paste by mixing S3, particle dispersion liquid and The one-dimensional nanomaterial dispersion By preparing a mixed solution containing , forming at least one corresponding paste.
[0078] Specifically, the ceramics obtained in S1 particle The dispersion is mixed with the one-dimensional nanomaterial dispersion obtained in S2, and the mixing method is high-speed stirring, high-pressure homogenization, sand mill dispersion, etc. Next, an adhesive is added to the mixed solution. The adhesive is at least one of polyvinyl alcohol, polyacrylonitrile, polyacrylic acid, styrene butadiene rubber, carboxymethyl cellulose, polyvinylidene fluoride, polyvinylpyrrolidone, and polyimide. The adhesive is In a mixed solution of ceramic particle dispersion and one-dimensional nanomaterial dispersion It accounts for 1% to 10% of the solid mass.
[0079] In the film formation by coating in S4, the at least one paste is coated onto the base film, and the base film and the paste are dried to obtain the coated separator.
[0080] Specifically, the prepared paste is coated on the base film by a coating method, and then dried to obtain a coated separator. The coating method can be spray coating, dip coating, microgravure coating, print coating, press coating, wire bar coating, etc. EitherThe base film is, for example, a polyolefin base film, the thickness of which is 3 to 30 microns, and the drying temperature is 40 to 130°C. ℃ and the coating speed is 10 to 200 m / min.
[0081] Here, as a preferred embodiment, ceramics particle Further including S11 to S12 before the dispersion of S11 Ceramics particle In the selection step, first ceramic particles and second ceramic particles having different particle sizes are selected, wherein the first ceramic particles have an average particle size of 10 to 60 nm, and the second ceramic particles have an average particle size of 100 to 600 nm; S12 Ceramics particle In the pretreatment, the first ceramic particles are added to a second solvent, then placed in a reaction vessel, and a grafting target is added to carry out a grafting reaction, thereby grafting lithium ion conductive functional groups onto the surfaces of the first ceramic particles. Specifically, the first ceramic particles are added to a second solvent, and then placed together in a reaction vessel, and the grafting target is further added, and the lithium ion conductive functional groups can be grafted onto the first ceramic particles at a certain reaction temperature, reaction pressure, and reaction time.
[0082] The first ceramic is not particularly limited, and is preferably a material having a melting point of 200° C. or more, high electrical insulation, and electrochemically stable within the range of use of the lithium battery. For example, ceramics such as oxide-based ceramics such as alumina, silica, titanium oxide, zirconia, magnesia, ceria, yttria, and zinc oxide, nitride-based ceramics such as silicon nitride, titanium nitride, and boron nitride, silicon carbide, calcium carbonate, magnesium sulfate, aluminum sulfate, basic alumina (aluminum hydroxide oxide), potassium titanate, talc, kaolinite, kaolin, nacrite, halloysite, pyrophyllite, montmorillonite, sericite, mica, amesite, bentonite, asbestos, zeolite, calcium silicate, magnesium silicate, diatomaceous earth, and silica sand may be used alone or in combination.
[0083] Second Ceramics particle The second solvent is not particularly limited, and is preferably a material having a melting point of 200°C or higher, high electrical insulation, and electrochemically stable within the range of use of the lithium battery, and may be the same or different inorganic material as the first ceramic. The second solvent may be water, ethanol, acetone, NMP, etc. Either The grafting targets are polycarbonate, polylactic acid, polyurethane, perfluoropropyl vinyl ether, methyl isopropyl ketone, etc. Either The reaction temperature is 100-200°C, the reaction pressure is 0.1-0.5Mpa, and the reaction time is 10-50min. After the reaction is completed, the liquid solvent is removed to leave a solid, which is a lithium ion conductive material. functional group Thus, first ceramic particles having the grafted thereto can be obtained.
[0084] Based on this, the ceramics in S1 particle Specifically, the variance of The first ceramic particles pretreated in S12 are mixed with the second ceramic particles and then dispersed in a first solvent to obtain a ceramic particle The aim is to obtain a dispersion.
[0085] The product performance of several embodiments of the present invention will be analyzed through experiments below.
[0086] Example 1 In this embodiment, a coated separator is obtained by manufacturing in accordance with the following steps S1 to S5.
[0087] S1 Ceramics particle In the selection, first ceramic particles and second ceramic particles having different particle sizes are selected, where the first ceramic particles have an average particle size of 40 nm and the second ceramic particles have an average particle size of 300 nm, and the first ceramic particles are particle and second ceramics particle All were alumina.
[0088] S2 Ceramics particle In the dispersion of the second ceramic particles, the first ceramic particles are mixed in a ratio of 1:1, and uniformly dispersed in N-methylpyrrolidone by a high-speed stirring method. particle A dispersion liquid was obtained. Ceramics particle The mass concentration of in the dispersion was 20%.
[0089] In the dispersion of one-dimensional nanomaterials in S3, one-dimensional nanomaterials of different lengths were dispersed in a dispersant to obtain a dispersion liquid. The dispersant was N-methylpyrrolidone, the dispersion method was high-speed stirring, and the mass concentration of the one-dimensional nanomaterials in the dispersion was 15%.
[0090] In the paste production by mixing S4, the ceramics obtained in S2 particle The dispersion is mixed with the one-dimensional nanomaterial dispersion obtained in S3, Form a mixed solution, The mixing method is high-speed stirring, and then the adhesive is added to the mixed solution. The adhesive is polyvinyl alcohol, and the adhesive is mixed solution It accounted for 8% of the solid mass in the mixture.
[0091] In the coating method of S5, the at least one paste is coated on a base film by a coating method, and the base film and the paste are dried to obtain the coated separator. Here, the base film is a polyethylene base film, the thickness is 9 microns, and the drying temperature is 100 ℃ The coating speed was 100 m / min. The thickness of the resulting coating layer was 2 microns.
[0092] Here, the one-dimensional nanomaterial is , Be The nanomaterials are deposited on the surface of the base film, forming a layered structure (i.e., layered 1D nanomaterials of different lengths). In the process of depositing on the base film, due to the surface energy, the longest 1D nanomaterial (which has the largest surface energy, is the most unstable, and is most likely to adhere once it comes into contact with an interface with a small surface energy) is deposited first, the second longest is deposited next, and the shortest is deposited next. 1D Nanomaterials was deposited last, and thus a layered structure was formed in which the layers were deposited gradually in order of length.
[0093] Examples 2 to 29 and Comparative Examples 1 to 5 are obtained using the same method, where the performance of the corresponding separators obtained in Examples 1 to 29 and Comparative Examples 1 to 5 is referred to Table 1, and except for the differences in the manufacturing parameters shown in Table 1, all the Examples and Comparative Examples are consistent with Example 1 in other respects, so the description is omitted.
[0094] However, in Example 30 shown in Table 1, S 1 Ceramics particle Before dispersion, ceramics particle The only difference from Example 1 is that the pretreatment step was performed. particleIn the pretreatment, the first ceramic particles are added to the second solvent, and then the mixture is put into a reaction vessel. The grafting material is added, and the reaction temperature, pressure, and time are kept constant to graft the lithium ion conductive functional groups onto the first ceramic particles. The second solvent is acetone, and the grafting material is polycarbonate. The reaction temperature is 150°C, the reaction pressure is 0.3Mpa, and the reaction time is 20min. After the reaction is completed, the liquid solvent is removed, leaving a solid, which gives the lithium ion conductive functional groups. functional group Thus, first ceramic particles having the grafted thereto can be obtained.
[0095] [Table 1-1] [Table 1-2] [Table 1-3]
[0096] As can be seen from Table 1, by comparing Examples 1 to 8, when there is too much one-dimensional nano material (Example 8), the lithium ion conductivity of the coated separator is much lower than other ratios, and when there is too much ceramic particles (Example 7), the battery capacity retention rate of the coated separator decreases and the thermal shrinkage decreases. When the ratio of one-dimensional nano material to ceramic is (1:1 to 1:14), as the ceramic occupation ratio increases, the battery capacity retention rate at high temperatures gradually decreases, the lithium ion conductivity gradually increases, the puncture resistance gradually improves, and the heat resistance gradually decreases. The main reason for this phenomenon is that as the occupation ratio of ceramic particles increases, coating The gap between the layers can be further expanded, further improving the lithium ion conductivity; however, larger voids result in stronger self-discharge and cause a decrease in capacity when stored at high temperatures. In addition, the expanded voids reduce contact between the coating layer materials, reducing heat resistance in a thermal environment. Furthermore, the puncture resistance of ceramic particles is superior to that of one-dimensional nanomaterials, improving puncture resistance.
[0097] As can be seen from the comparison of Examples 9 to 14, in the ceramics, the second ceramic particles (submicron ceramics particle As the proportion of the first ceramic particles (nano ceramics) increased (Examples 9 to 13), the lithium ion conductivity of the coating separator gradually increased, the battery capacity retention rate gradually decreased, the puncture resistance gradually increased, and the heat resistance remained unchanged. However, particle When the content of is too high (Example 9), the lithium ion conductivity of the coating separator is low and the puncture resistance is poor. The first Lamix particle When the content of was too low (Example 14), the heat resistance of the coated separator was high. The main cause of this phenomenon is The second Lamix particle is favorable for increasing the large porosity of the coating layer, which can improve the conductivity of the lithium battery; and Particle size big Second Ceramic particles have excellent puncture resistance, but the voids are large. Too much When the battery is left in a high temperature environment, self-discharge becomes stronger, causing a decrease in capacity. Also, the coating layer becomes thinner due to the expansion of voids. In Material-to-material contact Number of points The problem is that the thermal resistance in a hot environment decreases.
[0098] As can be seen from the comparison of Examples 15 to 27, 1. ceramic Particle When the particle size is too small (Example 24), the ionic conductivity of the coating separator becomes low, 1. Ceramics Particle When the particle size is too large (Example 25), the battery capacity retention rate of the coated separator is low, Second Ceramics particle When the particle size is too small (Example 26), the ionic conductivity of the coating separator is low and the puncture resistance is also reduced. Second Ceramics particleWhen the particle size was too large (Example 27), the battery capacity retention rate of the coated separator was low and the heat resistance was also reduced. The main cause of this phenomenon is 1. Ceramics particle If the particle size of First ceramic particles The aggregation problem becomes more severe, the lithium ion conduction channel becomes narrower, and the ionic conductivity becomes lower. 1. Ceramics particle If the particle size of the submicron ceramics is too large, the voids in the coating layer will become larger, further increasing self-discharge and decreasing the battery capacity retention rate. If the particle size of the submicron ceramics is too small, the voids in the coating layer will become narrower, the ionic conductivity will decrease, and the small size will weaken the ability to withstand external punctures. If the particle size of the submicron ceramics is too large, the voids in the coating layer will increase rapidly, resulting in a decrease in the battery capacity retention rate. In addition, the coating separator will become When exposed to heat This leads to a decrease in voids, which in turn leads to a decrease in heat resistance.
[0099] As can be seen from Comparative Examples 1 and 2, when only one-dimensional nanomaterials are present in the coating layer, the coated separator has excellent heat resistance, but poor lithium ion conductivity and puncture resistance; when only nanoceramics are present in the coating layer, the coated separator has poor heat resistance and puncture resistance, but excellent lithium ion conductivity; when only submicron ceramics are present in the coating layer, the coated separator has significantly poorer heat resistance and lower lithium ion conductivity, but high puncture resistance. As can be seen from the comparison of Examples 1 to 8, the one-dimensional nanomaterials and ceramics particle When the ratio of 1:1 was exceeded (Example 8), the lithium ion conductivity and puncture resistance of the coated separator did not improve. particle When the ratio was lower than 1:14 (Example 7), the lithium ion conductivity and puncture resistance of the coated separator were significantly improved, but the heat resistance was obviously reduced. particleand second ceramics particle When the ratio of the first ceramic to the second ceramic exceeds 6:1 (Example 9), the heat resistance and lithium ion conductivity of the coated separator are both high, but the puncture resistance is reduced. particle and second ceramics particle When the ratio was less than 1:6 (Example 13), the heat resistance and puncture resistance of the coated separator were improved, but the lithium ion conductivity was reduced. One-dimensional nanomaterial, first ceramic particles, and second ceramic particles of Between Only when the ratio is within a certain range, the coated separator shows the best overall performance in terms of each index (Example 5).
[0100] As can be seen from the comparison of Examples 1, 2, and 5 and Comparative Examples 3 to 5, when the one-dimensional nanomaterial is not hierarchical, the coated separator has low lithium conductivity and low battery capacity retention. The main reason for this phenomenon is that when the one-dimensional nanomaterial is not hierarchical, the aggregation phenomenon between the materials becomes very severe, and the aggregates block the pores of the base film, thereby causing low lithium ion conductivity, and the size of the voids is different, which causes the self-discharge problem to become severe, and further leads to a decrease in capacity retention.
[0101] In the description of this specification, the use of terms such as "one embodiment," "one example," "specific implementation process," and "one example" means that the specific features, structures, materials, or characteristics described with reference to the example or example are included in at least one example or example of the present invention. In this specification, exemplary descriptions of the above terms do not necessarily refer to the same example or example. In addition, the specific features, structures, materials, or characteristics described can be combined in any suitable manner in any one or more examples or examples.
[0102] Finally, it should be noted that the above embodiments are only for illustrating the technical solutions of the present invention, and are not intended to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art may still modify the technical solutions described in the above embodiments, or make equivalent substitutions for part or all of the technical features thereof, and such modifications or substitutions do not cause the essence of the corresponding technical solutions to depart from the scope of the technical solutions of the embodiments of the present invention. [Explanation of symbols]
[0103] 1-coating separator, 11-Base membrane, 12-coating layer structure, 13-Ceramic particles
Claims
1. A coated separator comprising a base membrane and a coating layer structure provided on at least one surface of the base membrane, the coating layer structure comprising multiple material layers, the coating layer structure comprising one-dimensional nanomaterials and ceramic particles, and characterized in that along a direction away from the base membrane, the average length of the one-dimensional nanomaterials in each material layer decreases with each layer.
2. 2. The coated separator according to claim 1, wherein the coating layer in which the ceramic particles are distributed accounts for 80% or more, preferably 90% or more, and more preferably 100% of the total thickness of the coating layer structure.
3. 3. The coated separator according to claim 1 or 2, wherein the mass ratio of the one-dimensional nano material to the ceramic particles in the coating layer structure is 1:1 to 1:
14.
4. The ceramic particles include first ceramic particles and second ceramic particles, wherein a particle diameter of the second ceramic particles is larger than a particle diameter of the first ceramic particles, and a particle diameter of the second ceramic particles is at least twice a diameter of the one-dimensional nanomaterial; Furthermore, the particle size of the second ceramic particles and the diameter of the one-dimensional nanomaterial are at least one order of magnitude different, and / or the particle diameter of the second ceramic particles is at least one order of magnitude different from the diameter of the first ceramic particles; The coated separator of claim 3, further characterized in that the one-dimensional nanomaterial has a diameter of 5 to 50 nm, the first ceramic particles have an average particle size of 10 to 60 nm, and the second ceramic particles have an average particle size of 100 to 600 nm.
5. 5. The coated separator according to claim 4, wherein in the coating layer structure, a mass ratio of the first ceramic particles to the second ceramic particles is 5:1 to 1:
5.
6. The coated separator according to claim 4, characterized in that the first ceramic particles and / or the second ceramic particles are inorganic substances having a melting point of 200°C or higher, having electrical insulation properties, and being electrochemically stable within the range of use of a lithium battery.
7. Lithium ion conductive functional groups are grafted onto the surfaces of the first ceramic particles; The coated separator according to any one of claims 1 to 5, further characterized in that the lithium ion conductive functional group includes any one of hydroxyl (-OH), carbonyl (-C=O), fluorine (-F) and carboxyl (-COOH).
8. The coating separator comprises at least a) puncture resistance of the coating layer ≧7N; b) ionic conductivity ≧0.8; c) Capacity retention rate ≧90%, d) thermal shrinkage at 180 ° C / h ≦ 4 %; 2. The coated separator according to claim 1, which satisfies any one of the following conditions:
9. A method for producing the coated separator according to any one of claims 1 to 8, comprising the steps of dispersing ceramics, dispersing one-dimensional nanomaterials, producing a paste by mixing, and forming a film by coating; In dispersing ceramics, ceramic particles are dispersed in a first solvent to obtain a ceramic dispersion; In dispersing one-dimensional nanomaterials, one-dimensional nanomaterials of different lengths are dispersed in the same or different dispersants to obtain at least one one-dimensional nanomaterial dispersion; In the preparation of the paste by mixing, the ceramic dispersion is mixed with the one-dimensional nanomaterial dispersion to form at least one corresponding paste; In the film formation by coating, the at least one paste is coated on at least one surface of the base film, followed by drying to obtain the coated separator.
10. Prior to dispersing the ceramics, further comprising a step of screening the ceramics; In the selection of ceramics, first ceramic particles and second ceramic particles having different particle sizes are selected, wherein the first ceramic particles have an average particle size of 10 to 60 nm and the second ceramic particles have an average particle size of 100 to 600 nm; The method for producing a coated separator according to claim 9, further comprising a step of pre-treating the ceramic, in which the first ceramic particles are added to a second solvent and then placed in a reaction vessel, and a grafting target is added to carry out a grafting reaction, thereby grafting lithium ion conductive functional groups onto the surfaces of the first ceramic particles.
11. The method for producing a coated separator according to claim 10, wherein the graft object includes any one of polycarbonate, polylactic acid, polyurethane, perfluoropropyl vinyl ether, and methyl isopropyl ketone.
12. Specifically, the dispersion of the ceramics is 11. The method for producing a coated separator according to claim 10, characterized in that the pretreated first ceramic particles and the second ceramic particles are mixed and then dispersed in a first solvent to obtain a ceramic dispersion.
13. A battery comprising the coated separator according to any one of claims 1 to 8 or the coated separator produced by the method for producing the coated separator according to any one of claims 9 to 12, The battery is further characterized in that the battery is a lithium battery.
Citation Information
Patent Citations
Improvements in or relating to storage batteries
GB580390A
Separator, method for producing separator and apparatus for producing separator
JP2013245428A
Separator for lithium ion secondary battery
JP2020145008A
Lithium-ion battery coating solution, lithium-ion battery separator, and lithium-ion battery
JP2021526299A